2000
DOI: 10.1152/jappl.2000.89.5.1837
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of caffeine and theophylline ingestion: exercise metabolism and endurance

Abstract: This two-part investigation compared the ergogenic and metabolic effects of theophylline and caffeine. Initially (part A), the ergogenic potential of theophylline on endurance exercise was investigated. Eight men cycled at 80% maximum O(2) consumption to exhaustion 90 min after ingesting either placebo (dextrose), caffeine (6 mg/kg; Caff), or theophylline (4.5 mg/kg Theolair; Theo). There was a significant increase in time to exhaustion in both the Caff (41.2+/-4.8 min) and Theo (37.4+/-5.0 min) trials compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
83
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 36 publications
(48 reference statements)
13
83
1
4
Order By: Relevance
“…These improvements are comparable to those reported by others (6,20,28,33) who have used a similar mode and intensity of exercise, as well as a similar dose of caffeine ingested 1-1.5 h before exercise. Furthermore, our findings 3 h after ingestion are consistent with a previous study by Flinn et al (12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These improvements are comparable to those reported by others (6,20,28,33) who have used a similar mode and intensity of exercise, as well as a similar dose of caffeine ingested 1-1.5 h before exercise. Furthermore, our findings 3 h after ingestion are consistent with a previous study by Flinn et al (12).…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, both the duration and magnitude of the ergogenic effect that followed a 5 mg/kg dose of caffeine were greater in the nonusers compared with the users. time to exhaustion; ergogenic aid; drug sensitivity THERE HAVE BEEN NUMEROUS STUDIES and reviews indicating that caffeine ingested before exercise causes rapid and significant improvements in performance, especially in aerobic exercise capacity (6,8,16,20,28,30). The dose of caffeine studied has ranged from 1 to 15 mg/kg of body mass.…”
mentioning
confidence: 99%
“…Several studies of younger individuals have found that caffeine increases endurance, e.g., in a crossover study by Graham and Spriet (15), 3 and 6 mg/kg caffeine increased endurance by 22% in well-trained athletes working at 85% of maximal oxygen consumption (V O 2 max ). Similarly, Greer et al (17) showed an endurance increase by 26% in subjects cycling at 80% V O 2 max after ingestion of 6 mg/kg caffeine. Pasman et al (33) also found that ingestion of 5 and 9 mg/kg of caffeine in well-trained athletes cycling to exhaustion at 80% V O 2 max increased endurance 23 and 26%, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…Experimentos controlados examinaram a farmacocinética e a dose-dependência da cafeína no repouso e durante o exercício (Grahan & Spriet 1991Jackman, 1996;Evans & Griffets, 1998); estes dados nos levaram à escolha da dose de 5 mg.Kg -1 , antevendo um aumento no rendimento físico dos atletas durante a experimentação. Embora não estivessemos interessados na medida da performance, acreditamos que a dose recomendada para avaliar os efeitos do fármaco no balanço eletrolítico deveria ser aquela que estivesse vinculada ao aumento do rendimento, conforme anteriormente descrito (Bell, 2002;Cox, 2002;Greer, 2000, Mohr, 1998.…”
Section: Resultsunclassified
“…Sua suplementação durante o esforço moderado eleva a atividade do eixo hipotalamicohipofi sário-adrenal e do sistema nervoso autonômico (Adler, 2000), diminuindo o tempo de reação ao estímulo (Kruk, 2001) e reduzindo a percepção ao esforço (Denadai & Denadai, 1998, Davis, 2003. Estudos têm demonstrado a atividade ergogênica da cafeína no exercício de endurance (Tarnopolsky, 1994(Tarnopolsky, , 2000Greer, 2000), causada provavelmente pelo retardo do aparecimento da fadiga e aumento do poder contrátil dos músculos esqueléticos e cardíaco (Applegate, 1999;Clarkson, 1996;Willians, 1995).…”
Section: Introductionunclassified